Within-Flock Population Dynamics of Dichelobacter nodosus - Smith, Edward M.; Gilbert, Andrew; Russell, Claire L.; Purdy, Kevin J.; Medley, Graham F.; Muzafar, Mohd; Grogono-Thomas, Rose; Green, Laura E. (Frontiers in Veterinary Science, 2017)
Footrot causes 70 – 90 % of lameness in sheep in Great Britain. With approximately 5 % of 18 million adult sheep lame at any one time, it costs the UK sheep industry £24 - 84 million per year. The Gram-negative anaerobe Dichelobacter nodosus is the causative agent, with disease severity influenced by bacterial load, virulence and climate. The aim of the current study was to characterise strains of D. nodosus isolated by culture from swabs from healthy and diseased feet of 99 ewes kept as a closed flock over a 10-month period; and investigate persistence and transmission of strains within feet, sheep and the flock. Overall 268 isolates were characterised into strains by serogroup, proline-glycine repeat (pgr) status and multilocus variable number tandem repeat analysis (MLVA). The culture collection contained 87 unique MLVA profiles and two major MLVA complexes that persisted over time. A subset of 189 isolates tested for the virulence marker aprV2 were all positive. The two MLVA complexes (76 and 114) comprised 62 and 22 MLVA types and 237 and 28 isolates respectively. Serogroups B and I, and pgrB were associated with MLVA complex 76, whereas serogroups D and H were associated with MLVA complex 114. We conclude that within-flock D. nodosus evolution appeared to be driven by clonal diversification. There was no association (P > 0.05) between serogroup, pgr or MLVA type and disease state of feet. Strains of D. nodosus clustered within sheep and were transmitted between ewes over time. D. nodosus was isolated at more than one timepoint from 21 feet, including five feet where the same strain was isolated on two occasions at an interval of 1 - 33 weeks. Collectively our results indicate that D. nodosus strains persisted in the flock, spread between sheep and possibly persisted on feet over time.